Knowledge, attitude and practices related to antibiotic use and resistance among students in Kurunegala and Kadugannawa midwifery training schools - Pamila Sadeeka Adikari; Shayanthini Silambanathan; Lelum Wannisinghe; Mihiri Thalgahagoda; Charith Wijethilake; Sandeep Lakshan (Journal of Health Technology Assessment in Midwifery, 2026)
Antibiotics are drugs designed to kill or inhibit the growth of harmful bacteria. They remain among the most significant advances in modern medicine for the management of bacterial infections. Antibiotic resistance (ABR) is a critical global health issue, severely exacerbated in low- and middle-income countries like Sri Lanka by factors such as over-the-counter sales, inappropriate prescriptions, and limited public awareness. Misuse, including self-medication and use for viral infections, is prevalent due to misconceptions. Public Health Midwives (PHM), as grassroots healthcare workers at the community level, directly influence antibiotic use. Developing PHMs with up-to-date knowledge on this aspect is vital to dispel misconceptions and promote responsible practices, empowering the audience to support educational efforts. This study aimed to assess the KAP regarding antibiotic use and resistance among students at midwifery training schools in Kurunegala and Kadugannawa. A cross-sectional descriptive study was conducted involving 140 PHM students, selected through stratified random sampling using a self-administered questionnaire. A remarkable 99.3% of respondents demonstrated high baseline awareness. However, 29.5% mistakenly believed antibiotics were effective against viral infections, highlighting common misconceptions. Knowledge of resistance mechanisms was notably inadequate, with 89.3% incorrectly assuming the human body becomes resistant. In contrast, 41.4% correctly identified that resistance develops through bacterial adaptation. While 98.6% followed the doctor's instructions, 40.4% resorted to self-medication. Additionally, 85.3% exhibited the correct attitude by completing the prescribed course, yet 23.6% prematurely discontinued their antibiotics. The study revealed that while PHM students had a general awareness of antibiotic use and ABR, significant knowledge gaps persisted. Misconceptions about the effectiveness and mechanisms of ABR development were common. Despite their positive attitudes, students displayed inconsistent practices. Targeted educational interventions are essential to address these gaps and can inspire the audience to advocate for curriculum enhancements and policy changes to bolster antibiotic stewardship.